Rancangan Turbin Angin Tipe Darrieush Menggunakan Analisis Banyak Sudu Pada Rotor Turbin - Gede Eka Lesmana; Ismail Ismail; Yohannes Dewanto (Jurnal Poli-Teknologi, 2012)
Abstract This paper discusses one of the renewable energy derived from wind, to be converted into electrical energy. One type of wind turbine is a vertical axis wind turbines. Of this type turbine utilize lift force on the blade airfoil to rotate. Rotor rotation speed is determined by the availability of wind magnitude and magnitude thrust the blade, so the installation of blade angle settings to be an interesting thing to study in order to obtain a high efficiency turbine designs. From the simulation results concluded that the rotor with two blades as the best configuration, the rate of increase in the largest lap, and has a torque greater than the rotor with three or four blades Keywords : Wind turbine, Blade, Rotor, Torque. Abstrak Makalah ini membahas salah satu energi terbarukan yang berasal dari angin, untuk dikonversi menjadi energi listrik. Salah aplikasinya adalah turbin angin sumbu vertikal. Turbin jenis ini memanfaatkan gaya angkat pada airfoil untuk memutar blade. Kecepatan putaran rotor ditentukan oleh besarnya angin, blade dan banyak blade, jadi pengaturan sudu blade menjadi hal yang menarik untuk mendapatkan desain turbin dengan efisiensi tinggi. Dari hasil simulasi dapat disimpulkan bahwa rotor dengan dua blade sebagai konfigurasi terbaik, tingkat kenaikan terbesar, dan memiliki torsi lebih besar dari rotor dengan tiga atau empat blade. Kata Kunci : Turbin Angin, Sudu, Rotor, Torsi